Analisis Perilaku Ekonomi Generasi Z Muslim dalam Berbelanja Online di E-Commerce dari Sudut Pandang Islam di Kecamatan Mamuju - Puti Manadasari; Syamsulbahri Syamsulbahri (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to analyse the economic behaviour in online shopping of generation Z Islam in Mamuju District from the perspective of Islamic consumption behaviour. The research method used is qualitative with a phenomenological approach. Data was collected through interviews with generation Z Muslim informants from five groups/communities in Mamuju Sub-district to explore their experiences in online shopping in e-commerce and how it is analysed from an Islamic perspective. The results showed that based on an Islamic perspective, the informants' consumption behaviour can be explained as follows: 1) They choose products based on cleanliness, quality, and authenticity. 2) Informants buy goods based on rating, price, description, user reviews, and bestseller status so that online transactions become transparent and honest. 3) Informants shop simply, according to their needs and financial capabilities, and shop 2-3 times per month on average. 4) Informants do not buy goods that are prohibited in Islam and help the economy. 5) They avoid impulsiveness by putting items in the basket first before buying, and the majority use the pay-on-site (COD) and ShopeePay methods to comply with religious rules. The conclusion of this study is that the majority of informants behave in accordance with consumption ethics in Islam, although there are a small number who are not yet in accordance due to the influence of changing times and lack of self-control in making economic decisions.